Fibrin Sheath Angioplasty: A Technique to Prevent Superior Vena Cava Stenosis Secondary to Dialysis Catheters - Hacker, Robert I.; Garcia, Lorena De Marco; Chawla, Ankur; Panetta, Thomas F. (International Journal of Angiology, 2012)
Fibrin sheaths are a heterogeneous matrix of cells and debris that form around catheters and are a known cause of central venous stenosis and catheter failure. A total of 50 cases of central venous catheter fibrin sheath angioplasty (FSA) after catheter removal or exchange are presented. A retrospective review of an outpatient office database identified 70 eligible patients over a 19-month period. After informed consent was obtained, the dialysis catheter exiting the skin was clamped, amputated, and a wire was inserted. The catheter was then removed and a 9-French sheath was inserted into the superior vena cava, a venogram was performed. If a fibrin sheath was present, angioplasty was performed using an 8 × 4 or 10 × 4 balloon along the entire length of the fibrin sheath. A completion venogram was performed to document obliteration of the sheath. During the study, 50 patients were diagnosed with a fibrin sheath, and 43 had no pre-existing central venous stenosis. After FSA, 39 of the 43 patient's (91%) central systems remained patent without the need for subsequent interventions; 3 patients (7%) developed subclavian stenoses requiring repeat angioplasty and stenting; 1 patent (2.3%) developed an occlusion requiring a reintervention. Seven patients with prior central stenosis required multiple angioplasties; five required stenting of their central lesions. Every patient had follow-up fistulograms to document long-term patency. We propose that FSA is a prudent and safe procedure that may help reduce the risk of central venous stenosis from fibrin sheaths due to central venous catheters.
Keywords: inferior vena cava thrombosis; percutaneous; proximal; renal failure; subclavian stenosis; vascular access; deep vein thrombosis